2017
DOI: 10.1093/humrep/dex028
|View full text |Cite|
|
Sign up to set email alerts
|

Soluble VCAM-1/soluble ICAM-1 ratio is a promising biomarker for diagnosing endometriosis

Abstract: The Ingrid Flick Foundation (Grant no. FA751C0801), which played no role in the study design, data collection and analysis, decision to publish or preparation of the manuscript. The authors declare no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 38 publications
2
49
1
Order By: Relevance
“…The expression of BCL6 (Evans-Hoeker et al, 2016 ) has been reported to be altered in secretory phase endometrial biopsies and may be useful diagnostically, but this approach will require invasive biopsy procedures. Other possible diagnostic markers for endometriosis include CA-125 (Hirsch et al, 2017 ), VEGF, microRNAs, immunologic markers, and soluble ICAM levels (Acimovic et al, 2016 ; Vodolazkaia et al, 2016 ; Gagné et al, 2003 ; Matalliotakis et al, 2001 ; Kuessel et al, 2017 ; Mosbah et al, 2016 ; Bohler et al, 2007 ; Drosdzol-Cop et al, 2012 ; Wu et al, 2015 ); however, none of these can identify endometriosis patients with both high sensitivity and specificity. It is clear that the need for a non-invasive diagnostic marker or method remains, and it would appear that the analysis of ME may offer a path to develop such tests.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of BCL6 (Evans-Hoeker et al, 2016 ) has been reported to be altered in secretory phase endometrial biopsies and may be useful diagnostically, but this approach will require invasive biopsy procedures. Other possible diagnostic markers for endometriosis include CA-125 (Hirsch et al, 2017 ), VEGF, microRNAs, immunologic markers, and soluble ICAM levels (Acimovic et al, 2016 ; Vodolazkaia et al, 2016 ; Gagné et al, 2003 ; Matalliotakis et al, 2001 ; Kuessel et al, 2017 ; Mosbah et al, 2016 ; Bohler et al, 2007 ; Drosdzol-Cop et al, 2012 ; Wu et al, 2015 ); however, none of these can identify endometriosis patients with both high sensitivity and specificity. It is clear that the need for a non-invasive diagnostic marker or method remains, and it would appear that the analysis of ME may offer a path to develop such tests.…”
Section: Discussionmentioning
confidence: 99%
“…ICAM1 is a cell surface glycoprotein, which binds to integrins [cycle of differentiation 11 (CD11)/CD18] to promote cell-cell adhesion. ICAM1 is regulated by STAT1 in type II serous papillary EC (36) and is elevated in endometriosis (37). Our previous study using the endometrial epithelial ECC-1 cells to model endometrial luminal epithelium during menstrual repair demonstrated galectin-7 at 2.5 µg/ml enhanced ECC-1 wound closure via integrin binding and upregulation of β-catenin, contactin and TGFβ1.…”
Section: Discussionmentioning
confidence: 94%
“…VCAM-1 and its counter receptors are expressed by both epithelial cells, such as eutopic and ectopic endometrial cells, and by cells of the immune system. Thus, VCAM-1 and its counter receptors may play roles in both the interaction between the endometrial cell and the peritoneal surface and the inflammation and immunological reaction that accompanies the disease process [46]. …”
Section: Discussionmentioning
confidence: 99%